Implicación de los NOx en la química atmosférica - Galán Madruga, David; Fernández Patier, Rosalía (M+A. Revista Electrónica de Medioambiente, 2006)
The aim of this article is to indicate the importance and implication that nitrogen oxides show in the atmospheric chemistry at a tropospheric level, pointing out the main role they develop in the formation of secondary pollutants really harmful for the human being such as ozone and nitric acid, differenciating to that purpose between a day and a night chemistry for these nitrogen oxides. In the same way it wish to state the main role of these compounds as indicators of the air quality in urban zones.
Keywords: Nitrogen oxides; Secondary pollutants and emission sources